The Finite Element Method in Heat Transfer and Fluid Dynamics, Third Edition. - Reddy, J. N. (Junuthula Narasimha), 1945- (CRC series in computational mechanics and applied analysis., 2010)
Equations of Heat Transfer and Fluid MechanicsPresent StudyMathematical PreliminariesGoverning Equations of a ContinuumGoverning Equations in Terms of Primitive VariablesPorous Flow EquationsLow-Speed Compressible Flow EquationsAuxiliary Transport EquationsChemically Reacting SystemsBoundary ConditionsChange of PhaseEnclosure RadiationSummary of EquationsThe Finite Element MethodModel Differential EquationFinite Element ApproximationWeighted-Integral Statements and Weak FormsFinite Element ModelInterpolation FunctionsAssembly of ElementsTime-Dependent ProblemsAxisymmetric ProblemsLibrary of Fi.